Type 1 Diabetes, Diabetic Nephropathy, and Pregnancy: A Systematic Review and Meta-Study (The Review of Diabetic Studies, 2023)
BACKGROUND: In the last decade, significant improvements have been achieved in maternal-fetal and diabetic care which make pregnancy possible in an increasing number of type 1 diabetic women with end-organ damage. Optimal counseling is important to make the advancements available to the relevant patients and to ensure the safety of mother and child. A systematic review will help to provide a survey of the available methods and to promote optimal counseling. OBJECTIVES: To review the literature on diabetic nephropathy and pregnancy in type 1 diabetes. METHODS: Medline, Embase, and the Cochrane Library were scanned in November 2012 (MESH, Emtree, and free terms on pregnancy and diabetic nephropathy). Studies were selected that report on pregnancy outcomes in type 1 diabetic patients with diabetic nephropathy in 1980-2012 (i.e. since the detection of microalbuminuria). Case reports with less than 5 cases and reports on kidney grafts were excluded. Paper selection and data extraction were performed in duplicate and matched for consistency. As the relevant reports were highly heterogeneous, we decided to perform a narrative review, with discussions oriented towards the period of publication. RESULTS: Of the 1058 references considered, 34 fulfilled the selection criteria, and one was added from reference lists. The number of cases considered in the reports, which generally involved single-center studies, ranged from 5 to 311. The following issues were significant: (i) the evidence is scattered over many reports of differing format and involving small series (only 2 included over 100 patients), (ii) definitions are non-homogeneous, (iii) risks for pregnancy-related adverse events are increased (preterm delivery, caesarean section, perinatal death, and stillbirth) and do not substantially change over time, except for stillbirth (from over 10% to about 5%), (iv) the increase in risks with nephropathy progression needs confirmation in large homogeneous series, (v) the newly reported increase in malformations in diabetic nephropathy underlines the need for further studies. CONCLUSIONS: The heterogeneous evidence from studies on diabetic nephropathy in pregnancy emphasizes the need for further perspective studies on this issue.